Sharing session by FSPU UiTM Sarawak Campus - “What It Takes to Publish A Book” - Mohamad Bohari, Asmah Alia (UiTM Sarawak, 2018)
Fakulti Senibina, Perancangan dan Ukur, UiTM Sarawak successfully organised a half-day Sharing Session - “What It Takes to Publish A Book” for 39 academic staff on 8 January 2018 at Bilik Sarjana, UiTM Samarahan Campus. The invited speaker, Dr. Md. Asrul Nasid Masrom successfully motivated the participants to publish by providing a few important steps and techniques in book publication. During the sharing session, Dr. Md. Asrul, who is also the Deputy Dean of Students’ and Alumni affairs of Technology and Business Management Faculty, UTHM, shared his experience, including the obstacles and challenges he faced to publish his book.